Modifikasi Pangan Lokal Berbahan Ikan Kepala Batu dalam Pencegahan Anemia Pada Ibu Hamil - Rahmadani, Rina; Budiana, Yazid (Universitas Haji Sumatera Utara, 2025)
The prevalence of anemia is still high, as evidenced by data from the World Health Organization (WHO) in 2016, the prevalence of anemia in pregnant women was 40.1%. Anemia in pregnancy is a national problem because it reflects the value of the socio-economic welfare of the community and affects the quality of human resources. Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. Ways to overcome and prevent anemia in pregnant women with pharmacological and non-pharmacological therapy. The high iron content in stonehead fish can be recommended as a non-pharmacological therapy to prevent anemia. To determine whether there is an effect of consuming stonehead fish nuggets on increasing hemoglobin (Hb) levels in pregnant women with anemia in Medan Belawan District. Quantitative research type with quasi-experimental research design with pretest and posttest two group design, research sample of 15 pregnant women with anemia, taken by purposive sampling. Statistical test Paired T-test, there is an effect of consuming stonehead fish nuggets on increasing hemoglobin levels of pregnant women with anemia with a ρ value of 0.000 <0.05. Statistical test Independent T-test, there is an effect of consuming stonehead fish nuggets (intervention group) (control group) on hemoglobin levels with a ρ-value of 0.00 <0.05.